Production of Curcumin-Olive Oil-Tween 80 Nanoemulsion Using Green Technology-Wet Ball Milling Method - Zubaidah Ningsih; Rahmadhani Mahvirotul Zulkarnain; Budi Kamulyan (Indonesian Journal of Environment and Sustainable Development, 2022)
Turmeric (Curcuma longa L) is one of the medicinal plants as a high sustainable source of curcumin which has various theurapeutic effects. Modification of curcumin in the form of nanoemulsion has been widely developed to increase it’s absorption in the body. A green technology method, wet ball milling, is one of the alternative methods in producing nanoemulsion. Our research highlights the application of wet ball milling in the production of curcumin-olive oil-Tween 80 nanoemulsion. This study aims to determine the effect of different concentrations of Tween 80 (5%, 8% and 10%) with milling time variation of 1, 4, 8 and 24 hours to the characteristics of nanoemulsion. Parameters measured are predicted particle size, encapsulation efficiency and system stability. Our results show that the optimum milling time of 5%, 8% and 10% Tween 80 are 4, 1 and 8 hours  with average predicted particle size of 88.9, 94.27 and 180.73 nm and encapsulation efficiency of 4.96%, 12.63% and 71.93%, respectively. Apparently, curcumin-olive oil-Tween 80 nanoemulsion system is less stable in storage for 30 days, however, storage at 4°C can maintain system stability better than at room temperature. Our research is succesfully produced curcumin-olive oil-Tween 80 nanoemulsion by applying wet ball milling method. Keywords: curcumin nanoemulsion, wet-ball milling, sustainable medicinal plants, green technology, Tween 80